Caffeine as a contaminant of concern: A review on concentrations and impacts in marine coastal systems. (January 2022) - Vieira, L.R.; Soares, A.M.V.M.; Freitas, R.
Abstract: Caffeine has been identified as emerging contaminant of concern due to its widespread occurrence in the aquatic environment and potential to be biologically active. Recently, these concerns have been translated in an increasing research on its occurrence and effects on biota. However, there is still a limited knowledge on seawater matrices and the implications of caffeine presence in coastal and marine ecosystems are not fully known. The present review aims to fill these knowledge gaps, analysing the existing literature regarding the occurrence, effects and potential risks of caffeine residues to coastal ecosystems, contributing to the risk assessment of this psychoactive drug in the aquatic environment. The analysed literature reported caffeine concentrations in the coastal ecosystems, raising high concerns about the potential adverse impacts on the ecological safety and human health. Caffeine has been found in tissues from coastal and marine biota including microalgae, coral reefs, bivalves and ﬁsh due to bioaccumulation after chronic, long-term exposures in a contaminated environment. Additionally, caffeine residues had been demonstrated to have adverse impacts on aquatic organisms, at environmentally realistic concentrations, inducing oxidative stress and lipid peroxidation, neurotoxicity, changing energy reserves and metabolic activity, affecting reproduction and development and, in some cases, causing mortality. Considering the increasing adverse impacts of caffeine pollution in the coastal environment, this review highlights the urgent need to minimize the increasing load of caffeine to the aquatic ecosystems; being imperative the implementation of scientific programs and projects to classify effectively the caffeine as a high-priority environmentally hazardous emerging pollutant. Highlights: Most of the studies on caffeine concentration in seawater are from the USA. Caffeine was detected in marine and coastal areas of 13 European countries. In Europe the highest caffeine concentration was found in the Aegean Sea (3068 ng/L). Caffeine was found in tissues of coastal taxa from contaminated environments.